Land-use changes and slope positions impact on the degradation of soil functions in nutrient stock within the Kalikungkuk micro watershed, East Java, Indonesia - Anita Dwy Fitria; S Sudarto; Syahrul Kurniawan (Journal of Degraded and Mining Lands Management, 2021)
Degradation of soil functions in storing and cycling nutrients may be related to topography and land-use change. The research aimed to analyze the impact of land-use changes and slope positions on soil function in nutrient stock within Kalikungkuk micro watershed of East Java, Indonesia. Four different land-uses such as vegetable crops, agroforestry, shrub and forest were selected with three slope positions (e.g. ridge, slope, and valley), and three replications of each. Soil samples were collected at 0-10, 10-30, 30-50, and 50-100 cm depth of soil. Variables measured included soil properties (e.g. bulk density, soil texture, pH, CEC, soil nutrients). Slope positions impact on differences in soil physical (i.e. soil bulk density, soil texture) and chemical (i.e. total N, exchangeable K) properties. In addition, forest conversion to other land-uses (i.e. agroforestry, shrub, vegetable crops) decreased soil nutrient concentration (i.e. total C, total N, Ca, Mg, Na), and consequently resulted in degradation of soil nutrient stocks of especially C and N. The strong positive correlation between soil nutrient stock (e.g. C and N) and vegetation cover such as canopy cover, basal area, and litter (r = 0.63 – 0.78, r table 1% = 0.39) showed the benefit of biodiversity in maintaining soil function on the nutrient stock.